Pengaruh Ekstrak Kembang Sepatu Sebagai Shampo Untuk Perawatan Rambut Rontok - Wulan Dari; Merita Yanita (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by damage to hair which causes hair loss. Several Padang State University students experienced abnormal hair loss. The way to treat hair loss is to use shampoo made from flower extract. The aim of this study was to analyze the effect of hair loss treatment using cosmetic hibiscus extract shampoo at a frequency of 2 days once and 3 days once used. This research uses pure experimental methods. The sample in this research was 6 cosmetology and beauty students from the class of 2023. Data collection techniques use observation methods, documentation and assessment sheets. The data analysis technique used is the normality test, homogeneity test and independent sample test with SPSS 26. The normality test results show a sig>0.01 value, namely 200, which is normally distributed. In the homogeneity test results, the value of sig>0.01, the Levene statistic result is 1.066, indicating that the results have a homogeneous variance. The results of the independent simple test using spss26 were nil. ai sig >0.01, namely 0.660, shows that there is a comparison between the effect of using shampoo from hibiscus extract in the 2 day 1 treatment with the 3 day 1 treatment. From the results of the effect of using hibiscus extract shampoo, treatment 2 days 1 time is more effective or faster to prevent hair loss.